PERANCANGAN IDENTITAS VISUAL KOPI BIASA X CLASSIC MILK SEBAGAI MEDIA BRANDING MELALUI AKTIVASI KENDARAAN FOODTRUCK VW KOMBI - Farrell Dzaki Wardhana; Aldrian Agusta (Jurnal Riset Multidisiplin Edukasi, 2025)
The coffee industry in Indonesia is currently experiencing rapid growth, with an increasing number of coffee shops and cafés, each with its own unique style. Seeing the public’s enthusiasm for the culture of hanging out and drinking coffee, Kedai Kopi Biasa (Kobi) x Classic Milk continues to develop in order to stay relevant to society. Kobi serves a variety of menus in a simple setting and plans to establish a quick-service coffee shop, recognizing that coffee has become a favorite beverage for accompanying daily activities. To ensure that the brand’s message reaches its audience, interaction between the brand and the public is essential. However, Kobi has not yet been able to fully communicate this. The current graphic elements consist only of a basic logo. Therefore, a redesign of the visual identity is needed to better attract the right target audience. One strategy is to utilize the food truck—already planned by the owner for sales—as both a selling platform and a promotional medium. To determine what type of visuals appeal to the audience, both qualitative and quantitative research methods were used. These methods aim to gather insights into the target audience and other fundamental information. Based on interview results, the owner hopes the brand’s identity and visual concept can be effectively conveyed. Therefore, the logo, visual assets, tone and manner, and other design elements should be tailored to the target audience. Supporting media such as packaging design, the food truck, and merchandise will be used to introduce the brand to the public.